The effect of stock prices, return on assets, and firm size on dividend payout ratio: evidence from Indonesian financial service companies - Mira Septiani; Nafiah Ariyani; Heri Ispriyahadi (Diponegoro International Journal of Business, 2020)
This paper aims to investigate the effect of stock prices, return on assets (ROA), and firms size on dividend payout ratio (DPR). We used 5-year annualized panel data from 2014 to 2018 of 17 financial sector companies listed in the Indonesian Stock of Exchange (IDX) as sample of this study. Analysis using three regression estimations (pooled OLS, fixed effects, and random effects) showed that stock price positively affects DPR. On the other hand,  both ROA and firm size has a negative effect on DPR. These result suggests that more substantial and higher profit companies prefer to retain their earnings for financing an investment as a growth opportunity than to distribute their income as a dividend. Thereby, this agrees with the pecking order theory.